تطوير المواد التعليمية على أساس المدخل الاتصالي في تنمية مهارة الكلام بالمدرسة المتوسطة الإسلامية الحكومية نجرونجوت (NGRONGGOT) نجانجوك (NGANJUK) - M Ayyub Mubtadi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
The purpose of this research to design teaching material based communicative approach to improve skill in arabic for students in Madrasah Tsanawiyah Negeri Ngronggot Nganjuk with regard to the needs and their characteristics. This research used the methods research and development based on development model borg and gall (1989). But procedure product development consisting of 10 step is: 1) potential and problem, 2) data collection, 3) the product design, 4) validation design, 5) revision design, 6) trial products, 7) revision products, 8) trial use, 9) revision products, and 10) mass production. From the trial last of the this development inconclusive as follows: 1) products teaching book has been developed systematically (based on a model borg and gall, 1989) and based on analysis empirical needs in the field, and already meet the criteria appropriateness and kemenarikan especially in aspect of the content and design learning after through the stage, analysis and revision based on input which is a constructive by experts. 2) useful in empirical field through pilot suitable for the user. This is shown by see through the survey given to teachers and students and tests the end of students, have turned out to be able to increase their study results students.